Air quality and life expectancy in the United States: An analysis of the moderating effect of income inequality - Terrence D. Hill; Andrew K. Jorgenson; Peter Ore; Kelly S. Balistreri; Brett Clark (Elsevier, 2019)
Although studies have shown that air pollution can be devastating to population health, little is known about the health implications of the intersection of air pollution and income inequality. We investigate if air pollution is especially detrimental to the health of US state populations characterized by more inequitable distributions of income. In other words, are the populations of states with higher levels of income inequality especially vulnerable to similar levels of air pollution? We use two-way fixed-effects panel regression techniques to analyze longitudinal data for 49 US states and the District of Columbia (2000-2010) to model state-level life expectancy as a function of fine particulate matter, income inequality, and other state-level factors. We estimate models with interaction terms to formally assess whether the association between fine particulate matter and life expectancy varies by level of state income inequality. Across multiple life expectancy outcomes and additive models, states with higher PM2.5 levels tend to exhibit lower average life expectancy. This general pattern is observed with our specifications for raw and weighted PM2.5 and with adjustments for income share of the top 10%, total population, GDP per capita, median household income, median age, percent college degree or higher, percent black, and percent Hispanic/Latino. We also find that the association between state PM2.5 levels and average life expectancy intensifies in states with higher levels of income inequality. More specifically, PM2.5 levels are more detrimental to population life expectancy in states where a higher percentage of income is concentrated in the top 10% of the state income distribution. We discuss the implications of our results for future research in social epidemiology and environmental justice. Keywords: Air quality, Particulate matter, Income inequality, Life expectancy, Social epidemiology